SYNTACTIC ANALYSIS OF SENTENCE PATTERNS AND TYPES OF BBC NEWS ARTICLES - Andriani, Erina; Bram, Barli (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
Sentence patterns and types play a crucial role in helping writers make their articles attractive. However, few studies analyzed the sentence patterns and types used in news articles. Therefore, this study aimed to explore the sentence patterns and types used in shaping news articles. The researchers used a syntactic analysis to examine the sentences. The data were collected from ten BBC news articles published in October 2020. The purposive sampling was used, and the data gathering instrument was structured observation sheets. The gathered data were calculated using percentages. The results showed five sentence patterns used, namely S+V, S+LV+SC, S+V+O, S+V+DO+OC, and S+V+IO+DO. It was also found that four sentence types, namely simple, compound, complex, and compound-complex sentences, were used. Among the used sentence patterns, S+V+O was the most frequent (42%), and the most frequent sentence type was the complex sentence (52.6%).